The occurrence of microplastics in freshwater systems – preliminary results from Krakow (Poland) - Połeć, Marzena; Aleksander-Kwaterczak, Urszula; Wątor, Katarzyna; Kmiecik, Ewa (Geology, Geophysics and Environment, 2018)
The results of research conducted in recent years indicates that microplastic particles are widely distributed in the aquatic environment. The investigations are mostly focused on marine waters and there is still a lack of information about their presence in both surface water and groundwater. In this paper, preliminary results of research conducted in Poland are presented. Different types of water samples were collected. Five litres of each sample were filtered through 0.4 μm glass fibre filters. In the first stage, visual identification was conducted using a stereomicroscope. Additionally, some interesting fragments were examined by means of SEM/EDS method. In the case of rivers water samples, which were characterized by a high content of organic matter and minerals, the visibility of microplastics could be reduced. In the sample from the Vistula River, some particles similar to microplastics were found. In the groundwater samples, some blue and green particles which supposed to be plastic were found by the stereomicroscope. Additional analysis with the DXR Raman Microscope method gave no clear results. The samples were too small and the plastic particles were very dispersed which prevented correct analysis. SEM analysis showed irregularly shaped particles which were considered to be microplastics. Considering the chemical composition, carbon predominated.